The Epidemiology of Dengue Fever: Comparative Analysis of Urban and Rural Transmission Dynamics - Mawikli, Easa Saiban; Murir, Abdullah Ibrahim; Alhusayni, Mohammed; Aldosari, Mubarak Saad Zuraib; Alhejaili, Abdullah Obaed Wasel; Alzamil, Mohammed Ibrahim; Hijan, Sami Mohmed Ahmed; Sabi , Jalal Ahmed Mohammed; Shaqarah, Samiali Mohammed; Ali, Mohammed Jaber Abdullah; Alyousef, Abdulkarim Abdulaziz Mahmad; Alamri, Ali Ahmed Ali; et al. (Journal of Ecohumanism, 2024)
Background: Dengue fever poses a significant public health challenge, with over 3 billion individuals at risk globally. Traditionally, urban environments have been associated with higher dengue transmission rates, primarily due to dense populations and favorable conditions for Aedes aegypti proliferation. However, recent studies indicate a notable increase in dengue prevalence in rural areas. Methods: This study conducted a comprehensive literature review, employing Medical Subject Headings (MeSH) and keyword searches across multiple databases, including PubMed, Embase, and Web of Science. The analysis focused on defining rurality, examining transmission mechanisms, and comparing dengue incidence between urban and rural settings. Results: The findings reveal that dengue transmission risk in rural regions often equals or exceeds that in urban areas. Variability in definitions of rurality complicates the assessment of dengue dynamics. Many rural areas exhibit characteristics traditionally linked to urban settings, such as increased human mobility and altered land use patterns, which can enhance vector breeding sites and transmission rates. Conclusion: The study underscores the necessity for enhanced surveillance and understanding of dengue transmission in rural contexts. It emphasizes that while population size is relevant, environmental and infrastructural factors significantly influence dengue risk. Effective public health interventions must address these complexities, especially as rural areas increasingly contribute to dengue epidemiology.